Propagation and conservation of native forest genetic resources of medicinal use by means of in vitro and ex vitro techniques - Sharry, Sandra Elizabeth (2011)
In Argentina, there are numerous native species which are an important source of natural products and which are traditionally used in medicinal applications. Some of these species are going through an intense extraction process in their natural habitat which may affect their genetic diversity. The aim of this study was to establish vegetative propagation systems for three native forestal species of medicinal interest. This will allow the rapid obtainment of plants to preserve the germplasm. This study included the following species which are widely used in folk medicine and its applications: Erythrina crista-galli or "seibo" (astringent, used for its cicatrizant properties and for bronchiolitic problems); Acacia caven or "espinillo" (antirheumatic, digestive, diuretic and with cicatrizant properties) and Salix humboldtiana or "sauce criollo" (antipyretic, sedative, antispasmodic, astringent). The methodology included the micropropagation of seibo, macro and micropropagation of Salix humboldtiana and the somatic embryogenesis of Acacia caven. The protocol for seibo regeneration was adjusted from nodal sections of seedlings which were obtained from seeds germinated in vitro. The macropropagation through rooted cuttings of "sauce criollo" was achieved and complete plants of this same species were obtained through both direct and indirect organogenesis using in vitro cultures. The somatic embryogenesis for Acacia caven was optimized and this led to obtain a high percentage of embryos in different stages of development. We are able to support the conservation of native forest resources of medicinal use by means of vegetative propagation techniques.